2022
DOI: 10.1007/s11104-021-05278-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of selected trace and rare earth elements to Juncus effusus L.: the potential role of de-icing chlorides in the roadside environment

Abstract: Background and aim The presence of chlorides in soils, e.g., from de-icing salts may change metal availability to plants. Methods To assess the role of de-icing chlorides on bioavailability of metals, the samples of the rhizosphere soils, roots and shoots of Juncus effusus L. were collected monthly from April to June of 2019 in the vicinity of roads and analyzed for trace (Ag, Cd, Co, Cu, Pb, Zn) and rare earth elements (from La to Lu). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…More factors discussed are interconnected and exhibit seasonal and temporal variations (Cánovas et al, 2023). Research has even found that such factors also include chloride complexes, which has a direct consequence on metals bioavailability, although the process itself and its effectiveness depend on a number of features, such as type of flora or the species, initial concentrations, nature of habitat (Dołęgowska et al, 2022). Also, the concentrations of bioavailable metals depend significantly on the types of chemical extractants .…”
Section: Bioavailabilitymentioning
confidence: 99%
“…More factors discussed are interconnected and exhibit seasonal and temporal variations (Cánovas et al, 2023). Research has even found that such factors also include chloride complexes, which has a direct consequence on metals bioavailability, although the process itself and its effectiveness depend on a number of features, such as type of flora or the species, initial concentrations, nature of habitat (Dołęgowska et al, 2022). Also, the concentrations of bioavailable metals depend significantly on the types of chemical extractants .…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Moreover, salinity has been found to both increase and decrease the bioavailability of metals (Greger et al 1995 ). Sodium promotes the desorption of metal ions bound to soil and sediment particles (Dołęgowska et al 2022 ; Du Laing et al 2008 ; Greger et al 1995 ). Chloride promotes the formation of soluble metal-Cl complexes, increasing the metal bioavailability, or less soluble metal-Cl complexes, lowering the metal bioavailability (Dołęgowska et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium promotes the desorption of metal ions bound to soil and sediment particles (Dołęgowska et al 2022 ; Du Laing et al 2008 ; Greger et al 1995 ). Chloride promotes the formation of soluble metal-Cl complexes, increasing the metal bioavailability, or less soluble metal-Cl complexes, lowering the metal bioavailability (Dołęgowska et al 2022 ). The combined effect of salinity’s often positive effects on bioavailability and negative effects on plant health results in both increased and decreased plant uptake of heavy metals (Dołęgowska et al 2022 ; Du Laing et al 2008 ; Fritioff et al 2005 ; Greger et al 1995 ; Han et al 2012a ; Szota et al 2015 ; Zhou et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.3 Uptake and accumulation of Zn by plantsAverage concentrations of Zn were higher in the roots of Iris pseudacorus L. plants than in the roots of Juncus effusus L. which indicates that Iris pseudacorus L. can accumulate higher concentrations of Zn than the Juncus effusus L. However, the overall results showed that both species signi cantly accumulated dissolved Zn. Zinc concentrations were mostly distributed in root tissues of Juncus and Iris plants, suggesting that the Zn distribution in plant parts usually follow this pattern: roots > foliage > branch > trunk(Hong et al 2005), respectively concentration sequence of the HMs are mostly as follows: rhizosphere soils > roots > shoots(Dołęgowska et al 2022). The biologically active, high surface area formed by plant roots that are rapidly growing, can be extremely active in absorbing pollutants from water(Raskin et al 1997).…”
mentioning
confidence: 99%